Bsbsbbs a. Ababbabababbsbs
Answer: 19.9248588452
Step-by-step explanation:
Answer:
1200
Step-by-step explanation:
ghgvhjhv g fty ftvyuibn
![Y= x^2 -5](https://tex.z-dn.net/?f=Y%3D%20x%5E2%20-5)
We need to solve for x, we need to get x alone
![Y= x^2 -5](https://tex.z-dn.net/?f=Y%3D%20x%5E2%20-5)
Lets start by removing -5
Add 5 on both sides
![y + 5= x^2 -5 + 5](https://tex.z-dn.net/?f=y%20%2B%205%3D%20x%5E2%20-5%20%2B%205)
![y + 5= x^2](https://tex.z-dn.net/?f=y%20%2B%205%3D%20x%5E2)
Now to isolate x , we need to remove the square from x
To remove square , take square root on both sides
![+-\sqrt{y+5} = \sqrt{x^2}](https://tex.z-dn.net/?f=%2B-%5Csqrt%7By%2B5%7D%20%3D%20%5Csqrt%7Bx%5E2%7D)
square and square root will get cancelled
![+-\sqrt{y+5} = x](https://tex.z-dn.net/?f=%2B-%5Csqrt%7By%2B5%7D%20%3D%20x)
So
and ![x = -\sqrt{y+5}](https://tex.z-dn.net/?f=x%20%3D%20-%5Csqrt%7By%2B5%7D)
Answer:
Alexander is incorrect because the expressions are not equivalent.
Step-by-step explanation:
If the expression is evaluated for any value of x, y; the result will not be same.
For instance, let assume x = 1 and y = 2
3x + 4y = 3 + 4 = 7
(3)(4) + xy = (3)(4) + (1 * 2) = 12 + 2 = 14
So, the expressions are not the same and Alexander is incorrect.